PARTISIPASI MASYARAKAT DALAM PENGELOLAAN BANK SAMPAH APIK AMANAH KELURAHAN LANGENSARI KABUPATEN SEMARANG - Kiki Oktaviana; Hardi Warsono; Endang Larasati Setianingsih (Journal of Public Policy and Management Review, 2022)
Until now, the government has not been able to overcome the problem of waste management. Therefore, the waste bank program was formed to create a community participation-based waste management system. One of the areas in Semarang Regency that implements the program is Langensari Village by forming the Apik Amanah Waste Bank, but community participation is suspected to be not optimal. This study aims to describe community participation in the Apik Amanah Waste Bank, identify factors related to community participation and analyze the efforts that have been made to increase participation. The approach used is descriptive qualitative with data collection techniques through interviews, observation and documentation. The results of the study show that the community participates in decision-making enough, but in implementation, utilization of results and evaluation is not optimal. The level of community participation is at a pseudo degree (tokenism). The driving factors for community participation are knowledge, support from the government and community leaders, competent waste bank human resources and the acquisition of incentives, while the inhibiting factors are work and limited infrastructure. Efforts to increase community participation are carried out by establishing regulations; appeals through the Regent's SE, 3R campaigns, invitations by waste bank administrators; and education through the Adiwiyata School Program and outreach